10 Years of Mohs Micrographic Surgery in Denmark: Results from a Nationwide Cohort - Yuki M.F. Andersen; Katrine Karmisholt; Trine Høgsberg; Mia-Louise Nielsen; Amanda Brosbøl; Sascha Stave; Louise Schøsler; Silje Omland; Christine Aarenstrup Daugaard; Martin Glud (Acta Dermato-Venereologica)
Basal cell carcinoma is the most common skin malignancy and constitutes a burden for patients and society. Mohs micrographic surgery is a recommended treatment for high-risk basal cell carcinoma, but long-term outcomes of Mohs micrographic surgery in Denmark are unknown. This study aimed to estimate the 5-year recurrence rate of basal cell carcinoma following Mohs micrographic surgery, and to investigate patient and procedure characteristics since the introduction of the procedure in Denmark. The Danish Registry for Mohs Surgery was established and all Mohs micrographic surgery cases nationwide from January 2012 to December 2022 were included. A total of 1,774 patients were included in the cohort, and 2,203 high-risk basal cell carcinomas were treated using Mohs micrographic surgery techniques. The overall 5-year recurrence of basal cell carcinoma following Mohs micrographic surgery was 3.8% (95% CI 2.8–5.0), 3.1% (95% CI 2.1–4.7) for primary basal cell carcinomas, and 5.3% (95% CI 3.6–7.8) for recurrent basal cell carcinomas. The primary basal cell carcinomas showed a tendency towards lower recurrence rates and better surgical outcomes than recurrent basal cell carcinomas, although not significantly. The recurrence rate estimates correspond to international levels, supporting Mohs micrographic surgery as a treatment option for high-risk basal cell carcinomas in Danish dermatological practice. The newly established patient registry serves as a cohort for future research in this field.